2015
DOI: 10.1136/bmj.h5876
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and recurrent haemorrhage associated with antithrombotic treatment after gastrointestinal bleeding in patients with atrial fibrillation: nationwide cohort study

Abstract: Study queStionWhat are the risks of all cause mortality, thromboembolism, major bleeding, and recurrent gastrointestinal bleeding associated with restarting antithrombotic treatment after gastrointestinal bleeding in patients with atrial fibrillation? MethodSThis Danish cohort study (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) included all patients with atrial fibrillation discharged from hospital after gastrointestinal bleeding while receiving antithro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 37 publications
(52 reference statements)
8
110
0
7
Order By: Relevance
“…Consistent with prior work, we found substantial rates of OAC discontinuation following major bleeding, despite increasing evidence that such discontinuations are associated with adverse clinical outcomes 11. In a retrospective analysis of 442 patients experiencing warfarin‐associated gastrointestinal bleeding, Witt et al reported warfarin discontinuation rates of 41.2% within 90 days of the index event.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with prior work, we found substantial rates of OAC discontinuation following major bleeding, despite increasing evidence that such discontinuations are associated with adverse clinical outcomes 11. In a retrospective analysis of 442 patients experiencing warfarin‐associated gastrointestinal bleeding, Witt et al reported warfarin discontinuation rates of 41.2% within 90 days of the index event.…”
Section: Discussionsupporting
confidence: 88%
“…Wiele przyczyn poważnych krwawień lub czynników wywołujących takie incydenty można leczyć lub wyeliminować, w tym źle kontrolowane nadciśnienie tętnicze, owrzodzenia trawienne oraz tętniaki wewnątrzczaszkowe. Ponowne rozpoczęcie leczenia przeciwzakrzepowego po incydencie krwawienia jest często uzasadnione klinicznie [460,510]. Trudne decyzje, w tym dotyczące przerwania i ponownego rozpoczęcia OAC, powinien podejmować wielodyscyplinarny zespół z uwzględnieniem oszacowanego ryzyka (ponownego) udaru i krwawienia, a także ryzyka krwawienia związanego ze stosowaniem różnych metod zapobiegania udarowi mózgu.…”
Section: Doustne Leczenie Przeciwzakrzepowe U Pacjentów Z Migotaniem unclassified
“…3 The optimum choice of anticoagulant therapy in a nonvalvular atrial fi brillation patient who wishes to resume anticoagulant therapy is debatable. 4,5 Outside the context of AUGIB a comparison between warfarin and direct oral anticoagulants (DOACs) showed that edoxaban 30 mg/d was associated with signifi cantly (p < 0.001) lower risk of gastrointestinal bleeding, 4 notwithstanding the recommendation that, when restarting oral anticoagulants after AUGIB 'if DOAC therapy is preferred apixaban is the preferred agent based on the most favourable rate of GIB (gastrointestinal bleeding) from clinical trials'. 5 The caveat is the lack of a reversal agent either for edoxaban or apixaban.…”
Section: Restarting Oral Anticoagulant Therapy After Acute Upper Gastmentioning
confidence: 99%
“…1 There is a growing body of evidence, including our own, 3 which supports the resumption of various classes of antithrombotics after AUGIB. 4 It should be emphasised that post-AUGIB mortality from uncontrolled exsanguination is rare, whereas mortality from major vascular events is common. 3,4 We believe that the vascular risks are amplifi ed after AUGIB due to a combination of factors including: i) induction of a prothrombotic state due to systemic stress, hospitalisation and transfusion, ii) cardiac strain associated with anaemia, which is prevalent after AUGIB, 1 and iii) the common practice of antithrombotic withdrawal.…”
Section: Antithrombotic Resumption After Acute Upper Gastrointestinalmentioning
confidence: 99%
See 1 more Smart Citation